Free love in the far north: plural breeding and polyandry of arctic foxes ( Alopex lagopus ) on Bylot Island, Nunavut - Carmichael, L.E.; Szor, G.; Berteaux, D.; Giroux, M.A.; Cameron, C.; Strobeck, C. (Canadian Journal of Zoology, 2007)
Molecular studies show that canid breeding systems are more complex than field data have sometimes suggested. For example, microsatellite DNA fingerprints of offspring and adults within their social group indicate that many canid species thought to form monogamous pairs engage in polygyny, polyandry, and plural breeding. In many areas, arctic foxes ( Alopex lagopus (L., 1758)) are considered monogamous, with the complexity of their social systems increasing as population isolation increases. We combined a genetic approach with spatial data of arctic foxes on Bylot Island, Nunavut, Canada, to investigate breeding patterns in a population less isolated than many previously studied. As in previous field studies, single breeding pairs were most common, but one case of plural breeding and one case of polyandry with multiple paternity were also observed. Reproductive output in arctic foxes is closely tied to the productivity of their habitat in a given year; we support the hypothesis that abundant resources at our study site have also contributed to complex breeding patterns among resident foxes. We also suggest that increased genetic variation among offspring of multiply mated females may provide an additional adaptive advantage to species in uncertain environments.